Comparative Analysis of Islamic and Modern Leadership: Challenges and Similarities (Al-Qamar, 2023)
This study conducts a comprehensive comparative analysis of Islamic Leadership and Modern Leadership paradigms, aiming to unearth their inherent challenges and shared principles. Islamic Leadership, rooted in religious teachings, emphasizes ethical conduct, service, and collective responsibility. It navigates the delicate balance between spiritual values and practical community needs. Modern Leadership, on the other hand, grapples with rapidly evolving global dynamics, including technological advancements and ethical dilemmas. Despite their distinct origins, both paradigms converge on the significance of ethics, service, and effective communication in leadership. This study sheds light on their nuanced intersections and offers valuable insights for leaders operating in diverse cultural and religious contexts. Understanding the challenges and similarities between these leadership models is crucial in fostering effective and ethical leadership practices in contemporary society.
Keywords: Islamic Leadership; Modern Leadership; Challenges and Similarities